The Extracellular Matrix and Biocompatible Materials in Glioblastoma Treatment - Belousov, Andrei; Titov, Sergei; Shved, Nikita; Garbuz, Mikhail; Malykin, Grigorii; Gulaia, Valeriia; Kagansky, Alexander; Kumeiko, Vadim (Frontiers in Bioengineering and Biotechnology, 2019)
During cancer genesis, the extracellular matrix (ECM) in the human brain undergoes important transformations, starting to resemble its embryonic state chemically, but with a much denser structure, which does not impede migrational capabilities of cancer cells though. The importance of the ECM role in normal brain tissues as well as in tumors has led to understanding that it can and should be viewed as a target and an instrument in the treatment of brain cancers. This review provides a detailed analysis of both experimental and applied approaches in combined therapy for gliomas. Matrix materials for glioblastoma treatment should have properties that allow them to be delivered into the body in various ways and in various forms, e.g., locally to the area of injury in the gel form and into the bloodstream in the form of polymer micelles, nanoparticles etc. Functional materials even without drugs or cells should mimic biomechanical properties of the native tissue, support vital functions, and slow down or stop the proliferation of surrounding cells for a prolonged period of time. The authors propose a two-step approach aimed, on the one hand, at elimination of the rest cancer cells remaining after tumor resection using an bioartificial matrix with relatively low modulus of elasticity and loaded with anticancer drugs, and on the other hand at restoring nervous tissue by injection of a matrix with a higher modulus of elasticity containing specific factors stimulating neurite outgrowth and regeneration.